2010
DOI: 10.1002/hyp.7797
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall partitioning and cloud water interception in native forest and invaded forest in Hawai'i Volcanoes National Park

Abstract: Abstract:In many Hawaiian forests, including cloud forests, native plant communities are being displaced by invasive tree species, possibly affecting rainfall partitioning and direct harvesting of cloud droplets by vegetation. In this study, the hydrological impacts of invasive species are examined, using measurements of rainfall (RF), throughfall (TF) and stemflow (SF), and estimation of wet-canopy evaporation and cloud water interception (CWI) by the canopy water balance approach in both native Metrosideros … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 50 publications
3
72
0
2
Order By: Relevance
“…Long-term patterns of decline in part correspond to shifts in the dominant plant species in high-elevation forests (Takahashi et al 2011). Comparisons between native forests and those dominated by invasive strawberry guava (Psidium cattleianum), for example, demonstrated that guava-dominated forests receive significantly less cloud water.…”
Section: Disruption Of Critical Dispersal Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term patterns of decline in part correspond to shifts in the dominant plant species in high-elevation forests (Takahashi et al 2011). Comparisons between native forests and those dominated by invasive strawberry guava (Psidium cattleianum), for example, demonstrated that guava-dominated forests receive significantly less cloud water.…”
Section: Disruption Of Critical Dispersal Pathwaysmentioning
confidence: 99%
“…Comparisons between native forests and those dominated by invasive strawberry guava (Psidium cattleianum), for example, demonstrated that guava-dominated forests receive significantly less cloud water. Guavadominated forests also have half the canopy water storage capacity of native forests (Takahashi et al 2011). All of these conditions can result in lower groundwater recharge and less stream channel discharge (Takahashi et al 2011).…”
Section: Disruption Of Critical Dispersal Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Canopy capacity was set at 0.05 inches, the mean of the average values reported for six forested sites in Hawai'i (DeLay, 2005, p. 42; Takahashi andothers, 2011, Safeeq andFares, 2014). Trunk-storage capacity was set at 0.01 inches, the mean of the values reported for four forest sites in Hawai'i (DeLay, 2005, p. 42; Safeeq and Fares, 2014).…”
Section: Forest-canopy Evaporation and Net Precipitationmentioning
confidence: 99%
“…It also included recent analyses of remote sensing and other studies of the strawberry guava invasion that strongly documented negative ecological effects of the weed (Asner et al, 2008;Zimmerman et al, 2008;Takahashi et al, 2011), an economic analysis of conventional control methods, and a cultural impact assessment (State of Hawaii, 2010). This document incorporated the many statewide consultations over the preceding two years, including inputs from public meetings.…”
Section: Regulatory Review Of Strawberry Guava Biological Controlmentioning
confidence: 99%